Researching New Social (Political) Movements as Protagonists of Social Engineering - Šuvaković, Uroš V. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
The article is a retrospective of the theoretical research of the sociologist Slobodan Antonic dedicated to evolution and strengthening of two important social (political) movements: radical-feminist and LGBT. Contesting the scientific-methodological basis of theories that “explain” them, the author emphasizes the importance of the neoliberal ideological platform on which these theories and derived movements are based. At the same time, numerous dangers that social engineering for which their members plead for are pointed out. Regardless the radical changes of social consciousness, social values and power relations in the contemporary society for which these movements plead for, they actually represent pro-systematic movements that help in preservation of neoliberal capitalism with their demands.